Various Stressors of Indonesian Nurses Working in The Netherlands: A Preliminary Study - Riftana, Ferry Dwi Cahya; Yusriani, Sri; Utomo, Kabul Wahyu; Gunarto, Muji; Sari, Novika Purnama (Universitas Muhammadiyah Yogyakarta, 2024)
Background: Working abroad certainly has challenges, especially when the job involves high responsibilities, such as being a nurse. The combination of the job tasks and the foreign environment potentially led to more stress, particularly for migrant nurses, including Indonesian nurses who work in the Netherlands.Objective: This study aims to explore the types of stress experienced by nurses from Indonesia working in the Netherlands.Methods: This qualitative research employed interview techniques and a literature review. The data were analyzed using coding systems in Microsoft Excel. Seven questions were used to conduct online interviews in October 2023 with five Indonesian nurses employed in the Netherlands. Simultaneously, a literature review was carried out by searching for publications on Wiley Online, Google Scholar, PubMed, Springer, and Science Direct. Journal articles found were then selected according to predetermined criteria. Seven questions were used to conduct interviews with five Indonesian nurses who were employed in the Netherlands.Results: The results of the interviews and literature review demonstrated that the types of stress for Indonesian nurses working in the Netherlands are physiological and psychological stress (in terms of the nature of the stressor), negative stress (in terms of the effect of stress on the individual), and acute stress (in terms of the duration of exposure to the stressor).Conclusion: Indonesian migrant nurses in the Netherlands experience physiological and psychological stress with negative effects, highlighting the need for further research with a larger sample size for more credible and diverse results.